A Performance Study of Different Approaches of Digital Image Compression Techniques - Mansouri, Wahida Ali; Hamda Othman, Salwa; Asklany, Somia; Elmorsi, Doaa Mohamed (Engineering, Technology & Applied Science Research, 2024)
Today, managing a large amount of information becomes increasingly crucial. Efficient storage and retrieval of digital data are essential for their effective utilization. This study investigates the efficacy of Spatial Domain Image Compression Techniques, which directly manipulate the original image to reduce its size by leveraging pixel spatial relationships. These techniques segment the image into blocks and process each block independently. Evaluation entails measuring perceptual quality through metrics, such as PSNR, WPSNR, NMSE, and SSIM applied to the compressed image. Experimental results provide a comparative analysis of the performance of these techniques.